Load analyser using conservative power theory - Souza, W. A.; Liberado, E. V.; Da Silva, L. C.P.; Paredes, H. K.M. [UNESP]; Marafão, F. P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper deals with the analysis and application of novel conformity factors, defined by means of the Conservative Power Theory (CPT), for the purpose of load analysis and characterization. Basically, such factors are able to describe the influence of different load characteristic on the power factor calculation and they are valid under generic load and supply voltage conditions. Moreover, the development of a flexible smart-meter prototype has been described, for it has been used to the experimental validation of all power components and conformity factors considered on the paper. © 2013 IEEE.
Keywords: Conservative Power Theory; Load Analyser; Power Meter; Power Quality; Power Theories; Smart Meter